MOTIVASI ORANG TUA MEMILIH SEKOLAH BERBASIS AGAMA DI KECAMATAN KEBASEN KABUPATEN BANYUMAS (STUDI KASUS PADA ORANG TUA DI MI RANDEGAN) - Sasikirana, Alfa Nuryahning; Fauzi, Agung; Soetrisnaadisendjaja, Denny (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
In the family there are family functions, one of which is the function of education. Parents as the main role in the family should fulfill the function of education for their children. One of the functions of education is the fulfillment of formal education such as schools and non-formal education such as religious education. The limitations of parents in providing educational functions for their children, especially religious education, make parents worried about the future of their children in today's developments. This study focuses on examining the factors that encourage parents to choose religion-based schools over public schools. The background of the problem from this research is the number of parents who choose the education of their sons and daughters in Islamic religious-based schools so that many public schools are less desirable. This research uses a qualitative approach with the type of field research where the research informants are parents who send their children to MI Randegan, Kebasen District, Banyumas Regency. The sampling technique used is the saturated sample technique where the informants of this study amounted to 15 parents who sent their children to MI Randegan, Kebasen District. While the data collection techniques using observation, interviews, and documentation. The research site is in the Kebasen sub-district, Banyumas district, Central Java province, where in fact the surrounding community is about parents sending their children to religion-based schools.